The impact of phthalates on asthma and chronic obstructive pulmonary disease: a comprehensive analysis based on network toxicology and molecular docking - Li, Ren; Zheng, Bingqing; Zhang, Yuqiong; He, Lu; Ren, Chaomin; Guan, Linlin; Yang, Huan; Tian, Jiayu; Chen, Xingyi; Shi, Dongxing; Zhao, Lifang; Zhang, Zhihong (Frontiers in Pharmacology, 2025)
IntroductionPhthalates (PAEs) are widely used plasticizers in polyvinyl chloride (PVC) products since the 1930s, and recent research indicates a significant association between exposure to these substances and the development and progression of asthma and chronic obstructive pulmonary disease (COPD). Understanding the underlying mechanisms is crucial due to their public health implications.MethodsIn this study, we utilized innovative network toxicology and molecular docking techniques to systematically examine the effects of seven typical phthalates on asthma and COPD. By integrating information from multiple databases, we identified key target genes linked to these compounds and conducted functional enrichment analyses to elucidate their roles in pathological processes.ResultsOur results demonstrate that these phthalates affect the pathogenesis of asthma and COPD by modulating various target genes, including PTGS2, MMP9, and CASP3, which are involved in essential biological pathways such as apoptosis and immune response. Interestingly, certain inflammation-related genes and signaling pathways displayed novel regulatory patterns when exposed to phthalates, revealing new pathological mechanisms. Molecular docking analyses further confirmed stable interactions between phthalates and essential target genes, providing molecular-level insights into their pathogenic mechanisms.DiscussionOverall, this study highlights the harmful impacts of these seven phthalates on asthma and COPD, establishing new connections between the compounds and disease-related genes, and emphasizing their relevance as emerging environmental toxins. These findings provide valuable perspectives for risk assessment and public health policy, underscoring the need for stricter regulations and interventions regarding phthalate exposure.